2021
DOI: 10.1038/s41598-021-00351-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of fibulin-5 insufficiency and prolapse progression on murine vaginal biomechanical function

Abstract: The vagina plays a critical role in supporting the pelvic organs and loss of support leads to pelvic organ prolapse. It is unknown what microstructural changes influence prolapse progression nor how decreased elastic fibers contributes to vaginal remodeling and smooth muscle contractility. The objective for this study was to evaluate the effect of fibulin-5 haploinsufficiency, and deficiency with progressive prolapse on the biaxial contractile and biomechanical function of the murine vagina. Vaginas from wildt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…KO mice functionally lack elastic fibers that provide mechanical support to soft tissues, limiting the ability of the ECM to recover from deformation in response to applied forces. Without functional and fully assembled elastic fibers, fibrillar collagen, which largely provides the ECM tensile strength, is left to bear increased loading distinct in KO compared to HET soft tissue [9]. Indeed, in vivo and in vitro fibulin-5 HET mouse cervices display significantly greater circumferential contractility than fibulin-5 KO mouse cervices [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KO mice functionally lack elastic fibers that provide mechanical support to soft tissues, limiting the ability of the ECM to recover from deformation in response to applied forces. Without functional and fully assembled elastic fibers, fibrillar collagen, which largely provides the ECM tensile strength, is left to bear increased loading distinct in KO compared to HET soft tissue [9]. Indeed, in vivo and in vitro fibulin-5 HET mouse cervices display significantly greater circumferential contractility than fibulin-5 KO mouse cervices [40].…”
Section: Discussionmentioning
confidence: 99%
“…Clark-Patterson et al . demonstrated significantly reduced collagen alignment ratio with respect to the circumferential and axial axes in KO murine vaginas compared to FBLN5 +/- (HET) murine vaginas [9]. Furthermore, Budatha et al .…”
Section: Introductionmentioning
confidence: 99%
“…Strong mechanical force may cause acute dilation, overstretch, or even fracture of the pelvic floor tissue during the second stage of labor, resulting in damage to pelvic floor tissue. The role of mechanical force injury in the pathogenesis of POP has been gradually uncovered in recent years [ 5 , [42] , [43] , [44] ]. Mechanical injury leads to oxidative stress in the pelvic floor support structure, causing ROS accumulation and ECM metabolic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Fibulin-5 is a glycoprotein produced in smooth muscle cells, fibroblasts, or vascular endothelial cells [ 7 ] that is responsible for proper elastic fiber formation [ 8 ]. Elastic fiber components such as elastin, fibulins, and fibrillins are critical to proper extracellular matrix (ECM) construction, contributing mechanical compliance and elasticity to the reproductive tract [ 9 ]. For example, loss of elastic fibers in arterial walls decreases collagen fiber undulation that affects the collagen fiber’s stiffening characteristics [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, collagen can be remodeled in the KO reproductive tract. Clark-Patterson et al demonstrated significantly reduced collagen alignment ratio with respect to the circumferential and axial axes in KO murine vaginas compared to FBLN5 +/- (HET) murine vaginas [ 9 ]. Furthermore, Budatha et al reported thin and contorted collagen fibers in murine KO vaginas [ 11 ].…”
Section: Introductionmentioning
confidence: 99%